Defeitos congênitos diagnosticados em ruminantes na região Sul do Rio Grande do Sul - Pereira, Clairton Marcolongo (2010)
Congenital defects and hereditary diseases in cattle, sheep and buffaloes were studied through a review of necropsy files of the Laboratório Regional de Diagnóstico (LRD) of the Faculdade of Veterinária of the Universidade Federal de Pelotas (UFPel) between 1978 and 2009. The occurrence of congenital defects and/or hereditary diseases in cattle, sheep and buffaloes were 0.89%, 0.36% e 7.55% respectively from all received material. The defects were classified according the affected system. From 48 of congenital defects and/or hereditary diseases observed in cattle 21 (43.75%) affected the skeletal system (chondrodysplasia, scoliosis, lateral deviation of mandible, palatoschisis and unclassified malformation) nine (18.75%) the central nervous system (hypoplasia of olfatory and frontal lobes, cerebellar cortical degeneration, spina bifida, congenital hypomielinogenesis, hereditary hypermetria, cerebellar hypoplasia and pachygiria), nine (18.75%) the muscular system (arthrogryposis), three (6.25%) the cardiovascular system (patent ductus arteriosus and unclassified malformation), one (2.08%) the lymphatic system (hereditary lymphatic hypoplasia), one (2.08%) o alimentary system (atresia ani) and one (2.08%) the eye (congenital cataract). In five cases (10.42%) different systems were affected (diprosopus and decephalus dipos dibraqius). In sheep all observed defects affected various systems (anomalous twins and aprosopia). Of eight cases of congenital defects/hereditary diseases diagnosed in buffaloes three (37.5%) affected the muscular system (arthrogriposis and double muscle), two (25%) the integument (mechanobullous dermatosis and albinism), one (12.5%) the central nervous system (hydranencephaly), one (12.5%) the central nervous system/ integument (hydranencephaly/albinism) and one (12.5%) the alimentary system (megaesofagus). It was concluded that the sporadic congenital defects cause little economical losses in cattle. Environmental congenital defects can cause losses in certain localized geographic areas or farms. The hereditary diseases were important by mortality of animals and by spread of undesirable genes in cattle breeding from milk production region in Southern Brazil. In sheep the congenital defects are rare. In water buffaloes the high prevalence of hereditary diseases was a consequence of the high consanguinity of herd and management measures need to be taken to avoid the spread of recessive genes that are difficult to control.